Penjadwalan Housekeepers Hotel Pada Era Pandemi COVID-19 dengan Pendekatan Goal Programming - Yoga Sutisna; Monika Hidayanti; Sudradjat Supian (LPPM UNIBI, 2022)
Housekeepers have an important role in hotel operations because cleanliness and comfort are the attractions of hotels, especially during the COVID-19 pandemic era. However, during the pandemic, many hotel industries experienced a decrease in the value of the Room Occupancy Rate(TPK), which forced several hotels to closed, including the West Java region. This resulted in several employees being laid off including the Housekeepers, therefore the scheduling had to be rearranged so that there was no reduction in staff. This research is intended to determine the scheduling of Housekeepers with the Goal Programming approach in the era of COVID-19 pandemic case study at Hotel R Bandung City. The difference during the COVID-19 pandemic was in the different number Housekeepers because there was a reduction during the pandemic, so that it cloud increase the workload for other Housekeepers. This is evidenced by the results of scheduling using LINGO 11.0 software which is adjusted to the objective function to minimize deviations in constraint. From the results obtained, the difference in the number of working hours and holidays for Housekeepers before and after the COVID-19 pandemic however gas deviation equal to zero.